Topografien des 20. Jahrhunderts Die memoriale Poetik des Stolperns in Haroldo de Campos' «Galáxias» - Wrobel, Jasmin (MIMESIS, 2020)
The polyphonic world poem Galáxias (1984) by Brazilian poet Haroldo de Campos has, to date, mainly been discussed in the broader context of concrete poetry and the Latin American neo-baroque. This book offers a completely new reading of the work as a poetic testimony to a century of catastrophes: references to traumatic historical events are embedded as 'stumbling blocks' in the text, guiding the reader towards a 'Poetics of Stumbling'.